Whole course of treatment of autoimmune progesterone dermatitis that had spontaneously resolved during pregnancy: A case report and review of the literature - Huang, Yepei; Ye, Sha; Bao, Xiaoyan; Yang, Ru; Huang, Jian (Frontiers in Immunology, 2022)
Anaphylaxis due to autoimmune progesterone dermatitis is a rare but severe allergic disease in women. The clinical manifestations of APD are diverse, and a proper understanding of the disease can help even diagnose and treat it. A case of autoimmune progesterone dermatitis related in our department is reported as follows. She developed a rash with severe pruritus that was highly consistent with her menstrual cycle without any trigger 10 years ago. Laboratory tests were unremarkable. But all the symptoms disappeared during her pregnancy and resurfaced after the miscarriage. Two years ago, after a positive progesterone intradermal test confirmed the diagnosis of PH, she was given mifepristone, contraceptives(OCPs), and skin embedding treatment, and her symptoms improved.